The cinema as a laboratory in the classroom: a semiotic revew of the film La lengua de las mariposas (The tongue of the butterflies) (Foro de Educacion, 2024)
The study approaches the cinema as a resource for the reconstruction of historical processes from the barthesian audio-visual hermeneutic, with the purpo- se of being used in the university education, in matters referring to the subject. It has been wanted to delimit of historical and geographic way the area to work, to a film, «La lengua de las mariposas» (The tongue of the butterflies) (Spain, 1999), in the context of the Spanish Civil War, for being the more important historical fact of century XX for this country. A qualitative filmic investigation based in the theoretical-methodological postulates proposed by Roland Barthes, about the subdivision of films from significant units support-morpheme (SM), soon to establish the routes of meaning by means of the grouping of these significant units in Lexias. Soon the filmic space from the 5 bar- thesian codes of meaning was analyzed: Hermeneutic, proairetic, semic, symbolic and cultural or referential.